IMF Staff Papers, Volume 49, No. 2 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2002)
This paper explores sources of the output collapse in Russia during transition. A modified growth-accounting framework is developed that takes into account changes in factor utilization that are typical of the transition process. The results indicate that declines in factor inputs and productivity were both important determinants of the output fall. The paper analyzes the behavior of real commodity prices over the 1862-1999 progress. It also examines whether average stocks of health and education are converging across countries, and calculates the speed of their convergence using data from 84 countries for 1970-90.